Aliphatic Long-Chain Polypyrophosphates as Biodegradable Polyethylene Mimics - Tee, Hisaschi T. (Macromolecules, 2019)
[Image: see text] Biodegradable polyethylene mimics have been synthesized by the introduction of pyrophosphate groups into the polymer backbone, allowing not only hydrolysis of the backbone but also further degradation by microorganisms. Because of cost, low weight, and good mechanical properties, the use of polyolefins has increased significantly in the past decades and has created many challenges in terms of disposal and their environmental impact. The durability and resistance to degradation make polyethylene difficult or impossible for nature to assimilate, thus making the degradability of polyolefins an essential topic of research. The biodegradable polypyrophosphate was prepared via acyclic diene metathesis polymerization of a diene monomer. The monomer is accessible via a three-step synthesis, in which the pyrophosphate was formed in the last step by DCC coupling of two phosphoric acid derivatives. This is the first report of a pyrophosphate group localized in an organic polymer backbone. The polypyrophosphate was characterized in detail by NMR spectroscopy, size exclusion chromatography, FTIR spectroscopy, differential scanning calorimetry, and thermogravimetry. X-ray diffraction was used to compare the crystallization structure in comparison to analogous polyphosphates showing poly(ethylene)-like structures. In spite of their hydrophobicity and water insolubility, the pyrophosphate groups exhibited fast hydrolysis, resulting in polymer degradation when films were immersed in water. Additionally, the hydrolyzed fragments were further biodegraded by microorganisms, rendering these PE mimics potential candidates for fast release of hydrophobic cargo, for example, in drug delivery applications.